Detection of circulating antigen in sera of patients with malayan 1ilariasis by sandwich ELISA using monoclonal antibody Fes7 - Soeyoko, Soeyoko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background. The living lymphatic filarial worm Brugia malayi releases physiologically protein materials in the malayan filariasis patients which is called circulating antigen. Based on the clinical symptoms and the demonstration of microfilariae in the blood smears, people who are living in the endemic area can be classified into 4 groups: symptomatic microfilaraemic, symptomatic amicrofilaraemic, asymptomatic microfilaraemic and asymptomatic amicrofilaraemic.Objectives. To detect circulating antigen in sera of each group of patients with malayan filariasis in endemic area.Methods. Circulating antigen in sera was detected by sandwich ELISA using monoclonal antibody Fesi.Result. By sandwich ELISA using monoclonal antibody Fesi, 100% of symptomatic microfilaraemic sera, 35.7% of symptomatic amicrofilaraemic sera, 89.2% of asymptomatic microfilaraemic sera and 26.3% of asymptomatic amicrofilaraemic sera were positive for circulating antigen.Conclusion. Detection of circulating antigen in sera of malayan filariasis patients could be used to support the diagnosis of malayan filariasis in some cases which were difficult to be diagnosed by conventional method based on clinical symptoms and the demonstration of microfilariae in the blood smears.Keywords: circulating antigen - sandwich ELISA - monoclonal antibody - sera - Brugia malayi - asymptomatic amicrofilaraemic.